Testing Moderating Effects for the Causal Structure Model of Self-Action-Outcome (SAO Model) - Ramle, Abid; Norida, Abdullah; Kalthom, Hussin; Rosli, Saadan; Mohamad, Bokhari (2015)
This study focuses on developing the Self-Action-Outcome (SAO) model and testing the moderating effects based on gender and academic performance. The SAO model examined the relationship between self-esteem, job-search intensity and career decision-making self-efficacy among graduating students. The instruments used to develop this model were, the Rosenberg Self-Esteem Scale, Job-Search Intensity Scale, and Career DecisionMaking Self-Efficacy Scale. Participants were recruited using a cluster sampling procedure. Data were collected using a self-reported questionnaire. Data collected from 678 graduating students were tested with confirmatory factor analysis to obtain three best-fit measurement models from the three latent variables. The results showed that the overall fit of the SAO model was adequate with CFI = .977, TLI = .971 and RMSEA = .048. The statistics indicate that the parameters were free from offending estimates, ranging from .52 to .90. The moderators‟ variables such as gender and academic performance did not moderate the hypothesized SAO model means that the hypothesized SAO model is a good model among graduating students. Implications of the findings for social work practice such as guidance counsellor, research, theory, policy and education were also discussed.